1999
DOI: 10.1038/sj.cdd.4400589
|View full text |Cite
|
Sign up to set email alerts
|

The proteolytic procaspase activation network: an in vitro analysis

Abstract: In general, apoptotic stimuli lead to activation of caspases. Once activated, a caspase can induce intracellular signaling pathways involving proteolytic activation of other caspase family members. We report the in vitro processing of eight murine procaspases by their enzymatically active counterparts. Caspase-8 processed all procaspases examined. Caspase-1 and -11 processed the effector caspases procaspase-3 and -7, and to a lesser extent procaspase-6. However, vice versa, none of the caspase-1-like procaspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
147
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(157 citation statements)
references
References 37 publications
7
147
3
Order By: Relevance
“…The small subunit was subsequently processed by caspase-3 at D330 to yield a p12 form. 15,18,22,37,38 In agreement with an earlier study, 12 caspase-2 was not processed in caspase-9 deficient Jurkat cells (Figure 2). Both z-VAD.fmk and caspase-7 but not caspase-6 siRNA (Figures 4 and 5) inhibited the processing of caspase-2.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The small subunit was subsequently processed by caspase-3 at D330 to yield a p12 form. 15,18,22,37,38 In agreement with an earlier study, 12 caspase-2 was not processed in caspase-9 deficient Jurkat cells (Figure 2). Both z-VAD.fmk and caspase-7 but not caspase-6 siRNA (Figures 4 and 5) inhibited the processing of caspase-2.…”
Section: Discussionsupporting
confidence: 92%
“…24 Furthermore, recombinant caspase-7 can also cleave both caspase-2 and -6. 15 To resolve this discrepancy, we examined the hierarchical ordering of caspases in intact cells after activation of the intrinsic pathway under physiological conditions using M-791, a caspase-3 specific inhibitor and siRNA of caspases in caspase-3-deficient MCF-7 cells. After initial mitochondrial perturbation, activated caspase-9 activates both effector caspase -3 and -7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase-2 is known as a substrate for both caspase-3 and caspase-8 [43,44]. Caspase-2 activation comprises the formation of PIDDosome complex including RIP-associated ICH-1/ ECD3 homologous protein with death domain (RAIDD) that have CARD and death domain (DD) and p53-induced protein with death domain (PIDD) [45].…”
Section: Caspase Family Membersmentioning
confidence: 99%
“…In various settings it has been found to be processed by caspase 3, situating it at a downstream point in the apoptotic pathway. [4][5][6][7] On the other hand, caspase 2 interacts through its prodomain with the adaptor molecules RAIDD/CRADD and ARC, [8][9][10][11] is processed early in certain apoptotic pathways 12 and upon overexpression activates the caspase 9/3 cascade. 13,14 More recent studies have suggested that caspase 2 acts upstream of cytochrome c release.…”
Section: Introductionmentioning
confidence: 99%